BROADCAST MONITORING AND COMMUNITY INVOLVEMENT IN KPID NTB PROGRAM IN WEST LOMBOK - Saudi, Yusron; Rahmawati, Endang; Fathurrijal; Nasr, Badlihisham Bin Mohd (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2024)
Monitoring of broadcasting content by various parties includes public awareness and participation to create a positive broadcasting atmosphere in Indonesia. This research uses a qualitative method that focuses on the Environmental Care Program by KPID NTB in Banyumulek Village, West Lombok. The results showed that KPID NTB succeeded in building public awareness and participation in monitoring broadcast content through media literacy activities in the Desa Peduli Penyiaran program. This is reflected in two indicators, namely the creation of effective communication between the community and various parties and the increasing number of complaint desks that enter KPID NTB.